Effectiveness of Prenatal Yoga on Sleep Quality and Reduction of Anxiety During Pregnancy: A Meta-Analysis - Aflahiyah, Shiva; Tamtono, Didik Gunawan; Prasetya, Hanung (Journal of Maternal and Child Health, 2020)
Background:Anxiety and sleep disorders du